PEMBERDAYAAN SUSU KEFIR DI POSYANDU DESA CIPADANG KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN PROVINSI LAMPUNG - Sutarto; Reni Indriyani; Siwi Meutia Sadewi; Cindi Pebrianti (LP2M Universitas Hasanuddin, 2023)
Kefir is a probiotic drink made from fermented milk at room temperature for health. Kefir is different from other fermented products. The benefits of kefir for health, especially as an immunomodulator, an immunomodulatory function to improve the immune system. The immune system works all the time; when the immune system decreases, it has the potential to get sick. Sick conditions will impact chronic nutrition, and regular food accompanied by illness complications is the direct cause of stunting. This community service aims to increase knowledge in the context of stunting prevention by empowering mothers of toddlers and health cadres to manufacture various kinds of kefir milk for MP-ASI for toddlers and MP-ASI in posyandu service activities. Technical implementation using counseling, measuring knowledge, and practice of making milk Kefir. The activities' performance was carried out on July 30, 2022, and continued monitoring on August 5-7, 2022. Characteristics of participants based on education level: 40% have high school education with a general age of 31-40 years (44%). Most of the participants, mothers of toddlers, had high school education, although three educated people did not graduate from elementary school. The level of knowledge made in 3 groups of values, after counseling for 2 hours of lessons (90 minutes) and discussion (question and answers) for 1 hour of classes (45 minutes) so that the tendency for groups with knowledge levels of values more than 80 to increase sharply and scores less than 80, tends to decrease drastically. — Kefir adalah minuman probiotik dari fermentasi susu pada suhu kamar untuk kesehatan. Kefir berbeda dari produk fermentasi lainnya. Manfaat kefir bagi kesehatan, khususnya sebagai imunomodulator, fungsi imunomodulator untuk memperbaiki sistem imun. Sistem imun bekerja setiap saat, ketika imun turun berpotensi sakit, kondisi sakit akan berdampak pada gizi kronis, gizi kronis yang disertai dengan komplikasi sakit merupakan penyebab langsung dari kejadian stunting. Tujuan pengabdian kepada masyarakat ini untuk meningkatan pengetahuan dalam rangka pencegahan stunting dengan pemberdayaan ibu balita dan kader kesehatan pada pembuatan berbagai aneka susu kefir untuk MP-ASI balita dan MP-ASI pada kegiatan pelayanan posyandu. Teknis pelaksanaan dengan dengan cara penyuluhan, pengukuran pengetahuan dan praktik pembuatan susu Kefir. Pelaksanaan kegiatan telah dilakukan pada tanggal 30 Juli 2022 dan dilanjutkan monitoring pada 5-7 Agustus 2022. Karakteristik peserta berdasarkan tingkat pendidikan 40% berpendidikan SMA dengan usia umumnya 31-40 tahun (44%). Sebagian besar peserta ibu balita berpendidikan SMA, meskipun ada 3 orang berpendidikan tidak lulus pendidikan sekolah dasar. tingkat pengetahuan yang dibuat dalam 3 kelompok nilai, setelah dilakukan penyuluhan selama 2 jam pelajaran (90 menit) dan diskusi (tanya jawab) selama 1 jam pelajaran (45 menit) sehingga kecenderungan kelompok tingkat pengetahuan nilai lebih dari 80 meningkat tajam dan nilai kurang dari 80, cenderung turun drastis.